2020
DOI: 10.1128/msystems.00876-19
|View full text |Cite
|
Sign up to set email alerts
|

Initial Mapping of the New York City Wastewater Virome

Abstract: Bacteriophages are abundant members of all microbiomes studied to date, influencing microbial communities through interactions with their bacterial hosts. Despite their functional importance and ubiquity, phages have been underexplored in urban environments compared to their bacterial counterparts. We profiled the viral communities in New York City (NYC) wastewater using metagenomic data collected in November 2014 from 14 wastewater treatment plants. We show that phages accounted for the largest viral componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 84 publications
(112 reference statements)
4
26
0
Order By: Relevance
“…In contrast, another study retrieved a minute concentration of viruses in wastewater [48]. Bacteriophages have been identified as the predominant members of the viral microbiomes studied [26,49]. They influence microbial communities through interactions with their specific bacterial hosts.…”
Section: Virusmentioning
confidence: 99%
“…In contrast, another study retrieved a minute concentration of viruses in wastewater [48]. Bacteriophages have been identified as the predominant members of the viral microbiomes studied [26,49]. They influence microbial communities through interactions with their specific bacterial hosts.…”
Section: Virusmentioning
confidence: 99%
“…S3). Interestingly, the bacteriophages whose taxonomic percentages were in the top three were Podoviridae, Siphoviridae and Myoviridae in Lake Fuxian, which coincided with those identi ed from the ocean virome GOV2.0 and wastewater viromes [7,18]. In Lake Fuxian, putative hosts for Myoviridae, Podoviridae and Siphoviridae were members of Caulobacter, Myxococcus and Enterobacteria.…”
Section: Resultsmentioning
confidence: 74%
“…In Lake Fuxian, putative hosts for Myoviridae, Podoviridae and Siphoviridae were members of Caulobacter, Myxococcus and Enterobacteria. In wastewater plants, the most abundant hosts were Acinetobacter, Arcobacter, and Moraxella [18]. This nding demonstrated that host structure could be more diverse than viral taxonomy structure among different habitats.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The oceans, which cover 71% of the Earth, are the most valuable resource for investigating the ecological and geographical diversity of viruses. However, to date, aquatic viromic studies tended to study phages but already showed enormous genetic diversity and ecological distributions (Roux, et al 2016; Vlok, et al 2019; Guajardo-Leiva, et al 2020; Gulino, et al 2020; Moon, et al 2020; Zhang, et al 2020). Although some studies included aquatic invertebrates (Magbanua, et al 2000; Thakur, et al 2002; Shi, et al 2016; Rosani, et al 2019), there is a lack of systematic study of these animals in a whole.…”
Section: Introductionmentioning
confidence: 99%